1999
DOI: 10.1007/bf02784244
|View full text |Cite
|
Sign up to set email alerts
|

INAA of trace elements in colorectal cancer patients

Abstract: The concentration of trace elements in samples of both colorectal cancer tumors and normal tissues of a Mexican population were irradiated for 30 s and 4 h and their elemental content were measured by instrumental neutron activation analysis. Ca, Cu, Co, I, Mg, Se, Fe, Zn, Hg, Ba, and Cr were analyzed. Alterations in Co, Fe, I, and Ba were found in tumors with respect to normal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…Only the data obtained by Martin Mateo and Martín4 were collected from subjects not affected by tumours. However, Al, Cd, Fe and Se biopsy concentrations agreed with those previously reported,5, 11, 12 and Ba, Co and Pb were of the same order of magnitude as previously reported data 11, 12. In contrast, the levels of Cu, Mg, Mn and Zn were generally higher than in earlier studies 3, 4, 6, 10, 11.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Only the data obtained by Martin Mateo and Martín4 were collected from subjects not affected by tumours. However, Al, Cd, Fe and Se biopsy concentrations agreed with those previously reported,5, 11, 12 and Ba, Co and Pb were of the same order of magnitude as previously reported data 11, 12. In contrast, the levels of Cu, Mg, Mn and Zn were generally higher than in earlier studies 3, 4, 6, 10, 11.…”
Section: Resultssupporting
confidence: 92%
“…However, Al, Cd, Fe and Se biopsy concentrations agreed with those previously reported,5, 11, 12 and Ba, Co and Pb were of the same order of magnitude as previously reported data 11, 12. In contrast, the levels of Cu, Mg, Mn and Zn were generally higher than in earlier studies 3, 4, 6, 10, 11. For Ca and Ni, the colon concentrations overlapped those observed in two previous studies,5, 12 but were much higher than those reported elsewhere 8, 10.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations